Camp cookery - McDowell, George Garfield (My University, 1900)
Introduction: General Egbert L. Viele, a veteran of the Mexican and Civil wars and numerous Indian campaigns, has well said: “A bad cook is a man’s worst enemy, and a soldier has more reason to dread this enemy of his health than the open enemy in the field.” This enemy, in conjunction with the various camp diseases, has proven a most disastrous one to all armies in the past. From statistics of comparative losses by bullet and by disease in past wars, it seems a wonder that a nation so far advanced in military science as the United States should give this ever present foe so little attention. It would, perhaps, be well to give the comparative losses in several modern wars, resulting from these two causes. [Table insert] These figures are all given in round numbers, and show that the losses resulting from disease in all late wars of any import, except of the Germans in the Franco-Prussian War, have been far greater than those resulting from the bullet. But you may ask what camp cookery has to do with bringing about these losses. I will give the views of two eminent authorities in the subject.
Citation: McDowell, George Garfield. Camp cookery. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Cooking; Camp Kitchens; Food Preparation; Military; Logistics; Theses